2007
DOI: 10.1016/j.mcn.2007.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Egr3, a synaptic activity regulated transcription factor that is essential for learning and memory

Abstract: Learning and memory depend upon poorly defined synaptic and intracellular modifications that occur in activated neurons. Mitogen activated protein kinase-extracellular regulated kinase (MAPK-ERK) signaling and de novo protein synthesis are essential aspects of enduring memory formation, but the precise effector molecules of MAPK-ERK signaling in neurons are not well defined. Early growth response (Egr) transcriptional regulators are examples of MAPK-ERK regulated genes and Egr1 (zif268) has been widely recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 45 publications
5
102
0
1
Order By: Relevance
“…For example, egr-1 expression was shown to be induced in the anterior cingulate cortex, the CA1 region of the hippocampus, and the shell of the nucleus accumbens during retrieval of contextual fear memories, and in the amygdala and the nucleus accumbens core during retrieval of contextual and cued fear memories (Hall et al, 2001;Thomas et al, 2002). Studies on knockout mice further showed that egr-1 was essential for the transition from short-to longterm plasticity and for the formation of long-term memories (Jones et al, 2001), and they confirmed a role for egr-1 in the reconsolidation of memory after retrieval (Bozon et al, 2003;Lee et al, 2004).Unlike egr-1-deficient mice that exhibit impairments in late-phase long-term potentiation (LTP) and long-term hippocampal-and amygdala-dependent memories, egr-3-deficient mice have deficits in both early-and late-phase hippocampal LTP as well as short-and long-term hippocampal-and amygdala-dependent learning and memory (Li et al, 2007).In contrast to egr-1 and egr-3, little is known about the specific roles of the related protein egr-2 in synaptic-plasticity-dependent processes. Egr-2 expression was shown to be robustly and sustainedly induced in the dentate gyrus following LTP-inducing perforant path stimulation suggesting that egr-2 plays a role in the maintenance of LTP (Williams et al, 1995).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…For example, egr-1 expression was shown to be induced in the anterior cingulate cortex, the CA1 region of the hippocampus, and the shell of the nucleus accumbens during retrieval of contextual fear memories, and in the amygdala and the nucleus accumbens core during retrieval of contextual and cued fear memories (Hall et al, 2001;Thomas et al, 2002). Studies on knockout mice further showed that egr-1 was essential for the transition from short-to longterm plasticity and for the formation of long-term memories (Jones et al, 2001), and they confirmed a role for egr-1 in the reconsolidation of memory after retrieval (Bozon et al, 2003;Lee et al, 2004).Unlike egr-1-deficient mice that exhibit impairments in late-phase long-term potentiation (LTP) and long-term hippocampal-and amygdala-dependent memories, egr-3-deficient mice have deficits in both early-and late-phase hippocampal LTP as well as short-and long-term hippocampal-and amygdala-dependent learning and memory (Li et al, 2007).In contrast to egr-1 and egr-3, little is known about the specific roles of the related protein egr-2 in synaptic-plasticity-dependent processes. Egr-2 expression was shown to be robustly and sustainedly induced in the dentate gyrus following LTP-inducing perforant path stimulation suggesting that egr-2 plays a role in the maintenance of LTP (Williams et al, 1995).…”
mentioning
confidence: 63%
“…Unlike egr-1-deficient mice that exhibit impairments in late-phase long-term potentiation (LTP) and long-term hippocampal-and amygdala-dependent memories, egr-3-deficient mice have deficits in both early-and late-phase hippocampal LTP as well as short-and long-term hippocampal-and amygdala-dependent learning and memory (Li et al, 2007).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The same mice did not show detectable alterations of fear conditioning when compared to their wild-type littermates on the training day (t 34 ¼ 0.324, P ¼ 0.92). Given that the employed training protocol results in subceiling freezing (Li et al, 2007), the observed effects on extinction were probably not due to differences in the strength of the conditioning memory. This possibility was further excluded in the subsequent pharmacological studies that were selectively performed after extinction tests (see below).…”
Section: Fear Extinction and Erk2 Activity Of Erk1-deficient Micementioning
confidence: 96%
“…This procedure resulted in a subceiling level of freezing that can be enhanced by repeated training trials (Li et al, 2007). Extinction began 24 h later and consisted of daily 3-min re-exposures of mice to the conditioning context in the absence of shock.…”
Section: Contextual Fear Conditioning and Extinctionmentioning
confidence: 99%
“…H, C, and M indicate birth age for humans, chimpanzees, and macaques, respectively. potentiation (Davis et al 2003;Flavell et al 2006;Shalizi et al 2006;Li et al 2007), raising the possibility that module 1 genes have roles in synaptic development and neuronal functions.…”
Section: Regulation Of Human-specific Expression Patternsmentioning
confidence: 99%